Medição instrumental de energia primária e secundária e sistematização da massa de dados gerada em sistema piloto eólico-solar - Gimenes, André Luiz Veiga; Linhares, Angélica Luana; Abreu Junior, Antônio Celso; Bernal, Jonathas Luiz Oliveira; Galvão, Luiz Claudio Ribeiro; Galvão, Martim Debs; Udaeta, Miguel Edgar Molares; Kanayama, Paulo Helio; Acebron, Rafael Martinez; de Paula, Raul Vaz [UNESP]; Carneiro, Rodrigo Antônio; Relva, Stefania Gomes; et al. (My University, 2018)
The objective of this work is to determine the specificities of the variables of the primary and secondary energy analysis process, considering a system of electrical generation by a wind power plant and by a solar photovoltaic power plant and the availability of data by a solarimetric station and by an anemometric station. In this sense, methodologically, the main measurement variables required, systemic and instrumental record for each physical unit are shown, resulting in the definition of the variables, their recording and integration intervals, raw and treated units, and the accumulation procedure of the mass data. It is concluded that the systematics for the case of photovoltaic and wind energy generation linked to scientific research must consider at least intervals of records every 1 minute for integration, thereby, the diagnosis of the seasonality of the measurements are easily verified; the important observations for the scientific study are produced, and the fundamental datasets for the development of the research are identified. Finally, it is important to highlight even considering this systematization, the good practice involves the complete storage of the data masses.
Instrumental measurement of primary and secondary energy and systematization of big-data generated in a pilot eolic-solar system
Keywords: Data mass; Measurement; Primary energy; Quantities; Secondary energy; Solar energy; Storage; Wind energy